An update on vitamin D for clinicians. Issue 6 (December 2016) - Hansen, Karen E.; Johnson, Michael G.
Abstract : Purpose of review: The clinical benefits of vitamin D therapy have received substantial attention over the past decade. Recently, several trials looked to clarify the optimal vitamin D dose or serum level needed to promote human health. The purpose of this review is to highlight selected studies published since January 2015. Recent findings: Several recent trials challenge whether serum vitamin D levels at least 30 ng/ml promote human health. In postmenopausal women with 25-hydroxyvitamin D [25(OH)D] levels 21 ± 3 ng/ml, high-dose vitamin D for 1 year increased calcium absorption by 1%, without changes in bone mineral density, physical function, or falls when compared with low-dose vitamin D and placebo. High-dose vitamin D increased risk of falling in 200 adults 78 ± 5 years old with baseline 25(OH)D levels of ∼19 ± 9 ng/ml. High-dose vitamin D in adults increased the number and duration of upper respiratory tract infections compared with placebo. Asthma patients achieving 25(OH)D levels more than 30 ng/ml during a trial experienced more respiratory infections than those not achieving such levels. Summary: Recent studies are congruent with the Institute of Medicine's conclusion that humans are vitamin D replete when their serum 25(OH)D levels are at least 20 ng/ml. Higher levels seem to promote falls and respiratory infections.